Daya Antibakteri Ekstrak Batang Pisang Ambon (Musa paradisiaca var. sapientum) terhadap Pertumbuhan Enterococcus faecalis - H. Hafizha; Ketut Suardita; Nirawati Pribadi (Universitas Airlangga, 2018)
Background: Enterococcus faecalis is one of the most common bacteria in root canal after endodontic treatment. This species is found in about 77% of the cases that resistant to treatment. It is necessary to develop an alternative for intracanal dressing, one of the potential substance is natural ingredients. The stem of ambonese banana (Musa paradisiaca var. sapientum) extract contains active substances such as tannin, flavonoid, alkaloid, saponin, and antraquinone, which have been known for their antibacterial potency. Purpose: The aim of this study was to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of ambonese banana stem (Musa paradisiaca var. sapientum) extract against Enterococcus faecalis. Method: This research was a laboratory experimental study. Ambonese banana stem extract was made by maceration method with ethanol 96% and certain dilution was performed to obtain various concentration. Value of MIC and MBC of ambonese banana stem extract against Enterococcus faecalis were known by counting the growth of bacteria colonies on blood agar media in CFU/ml. Result: The percentages of bacteria colonies at concentration 85%; 82,5%; 80%; 77,5%; 75%; 72,5%; 70%; and 67,5% of ambonese banana stem extract in sequence were 0%; 0%; 0%; 0%; 0%; 0%; 7,44%; and 14,53% from the positive control. Conclusion: The stem of ambonese banana (Musa paradisiaca var. sapientum) extract had minimum inhibitory concentration (MIC) at 70% concentration and minimum bactericidal concentration (MBC) at 72,5% concentration against Enterococcus faecalis.